Focus Group Discussion (FGD) Komunikasi Antar Budaya (Hospitality Desa Wisata Belitar Seberang Kecamatan Sindang Kelingi Kabupaten Rejang Lebong) - Risdiyanto, Bayu; Asnawati, Asnawati; Octaviani, Vethy (Universitas Dehasen Bengkulu, 2022)
Hospitality of Belitar Tourism Village is the attitude and behavior of hospitality in the relationship between guests and hosts as tourism service providers in Belitar Seberang Village, Sindang Kelingi District, Rejang Lebong Regency. The success of developing a tourist village, apart from being influenced by attractive tourist objects, is also strongly influenced by the attitudes and behavior of tourism managers and the surrounding community in providing services to visitors. This is a challenge for tourism managers considering that visitors come from various regions with various ethnic groups, languages ​​and cultural customs, so they are prone to communication errors. Therefore, the Dehasen University Bengkulu Communication Studies Program in collaboration with the Tourism Awareness Group as tourism managers in the Belitar Seberang Tourism Village, held a focus group discussion (FGD) on Intercultural Communication, especially related to the theme of hospitality in tourist villages. The FGD results show that the optimization of hospitality is influenced by: 1) Knowledge of the tourism management team about human personality traits, especially visitors. 2) Communication skills of the Tourism Management Team in serving visitors, 3) Existence of standard operating procedures (SOP) for tourism services in Tourism Villages. Based on these findings, it is suggested that there be hospitality training for the Belitar Seberang Village Tourism Management Team.